Analisis Pengaruh Ketersediaan Air Permukaan Terhadap Debit Mata Air - Sukmawati, Anak Agung Nila; Yudono, Andi Renata Ade; Gomareuzzaman, Muammar (Indonesian Journal Publisher, 2023)
Springs are one of the water sources that people can use to meet their clean water needs. The Balinese people in particular, apart from using spring water to fulfill their daily needs, also use it as a means of religious ceremonies so that its sustainability is strictly maintained. One of the springs that can be found in Bali is the Tirta Salaka spring. Tirta Salaka spring is located in Sading Village, Mengwi District, Badung Regency, Bali Province. The purpose of this study was to analyze the effect of surface water availability on Tirta Salaka springs. The method used in the research is a combination of quantitative and analytical methods. Based on calculations, the discharge value of the Tirta Salaka spring is smaller than the general water balance value from November to March. The discharge value of the Tirta Salaka spring from November 2022 to March 2023 is included in class VI with values of 1.111.931 liters/month, 1.196.208 liters/month, 1.413.677 liters/month, 1.036.800 liters/month, and 914.717 liters/month. This shows that the amount of discharge from the Tirta Salaka spring is influenced by rainfall. The higher the rainfall value, the higher the discharge of the Tirta Salaka spring